Integrated reporting and stakeholder management: a research agenda, - Anne Carolina dos Santos; Kelli Juliane Favato; Marguit Neumann (Revista Contabilidade & Finanças, 2021)
Abstract The purpose of this article was to propose an agenda for future research on stakeholder management in integrated reporting. Framework 1.0 of integrated reporting addresses the management of stakeholders as a routine in the course of business, without further details. In turn, the academy can contribute in this regard. Integrated reporting is a recent development achieved after 30 years (or more) of attempts to effectively expand accountability to stakeholders. The engagement with stakeholders produces successful results in the long term, highlighting the need to indicate to them the value of using integrated reports. Due to the absence of details in Framework 1.0, it is up to academics to actively and cautiously monitor its development and implementation. This article’s contribution is to raise research to bring the practice of integrated reporting closer, as well as generate discussions to involve academics, the International Integrated Reporting Council, national councils, and report writers. Thus, the integrated report was discussed considering that its framework must be updated (how to do it) to impact the practice (the act of doing it). For this, we used a bibliographic methodology and content analysis. We also used the literature review methodology and content analysis. We mapped 11 factors, established 10 qualitative propositions, and 35 insights for future studies. The results indicate that the stakeholder management may have reached its potential in a ceremonial way, but it lacks definitions. For the academy and the International Integrated Reporting Council, the study contributes by mapping factors and suggesting the implementation of guidelines and debates with local commissions to overcome the deficiencies pointed out by this study.